(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
The birth of tourism and the popularisation of photography at the end of the 19th century marked a turning point in the way of experiencing and documenting the world. While tourism emerged as a cultural practice that democratised access to travel, photography, mainly through KODAK’s product launches and marketing campaigns, was consolidated as an essential tool for capturing and sharing these experiences. Both disciplines fed off each other in their beginnings: tourism needed images that on the one hand promoted tourist destinations, and on the other made these places known to those who could not travel to them. For its part, KODAK found in tourism a practice with which to sell its products, or more specifically, on which to create a new need for the traveller: that of photographing the destinations visited. This text analyses both the birth of tourism and the rise of Kodak, in a similar time frame. In addition, some of Kodak’s most successful marketing campaigns are studied, all of them associated with tourism, or even generated by tourism itself. The text ends with an analysis of the “tourist gaze”, essential in our recent cultural history.